(3bUO GdEceGd HGdfXQ aj GdCaYGds - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfg deG cGf GdJhMjO dGjJe EdG HYO eYQaI Gddg HCfg hGMO ai PGJg hGMO ai CSeGFg hUaGJg hGMO ai CaYGdg heNdhbGJg hceG bO YQafG ef TQM CSeGFg GdMSfi s
(3BNQgG (B:s
(3ShQI Gdadb bhdg Yde HGdbde jYfi Ndb Gdbde hNdb GdYde hcfGjJg bhdg (B( (3Cde JYde HCf Gddg jQi (B) (3hbQjfkG ai GdeJhSW hGdebSW hZjQg hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B242s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs